2018
DOI: 10.3389/fmicb.2018.01338
|View full text |Cite
|
Sign up to set email alerts
|

Faba Bean (Vicia faba L.) Nodulating Rhizobia in Panxi, China, Are Diverse at Species, Plant Growth Promoting Ability, and Symbiosis Related Gene Levels

Abstract: We isolated 65 rhizobial strains from faba bean (Vicia faba L.) from Panxi, China, studied their plant growth promoting ability with nitrogen free hydroponics, genetic diversity with clustered analysis of combined ARDRA and IGS-RFLP, and phylogeny by sequence analyses of 16S rRNA gene, three housekeeping genes and symbiosis related genes. Eleven strains improved the plant shoot dry mass significantly comparing to that of not inoculated plants. According to the clustered analysis of combined ARDRA and IGS-RFLP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 46 publications
2
17
0
Order By: Relevance
“…Noteworthy, strains closely related to R. hidalgonense have also been isolated from other legumes including Acacia gummifera 78 , Indigofera arrecta in Ethiopia 3 , Trifolium spp. in Ethiopia 79 , T. semipilosum in Kenya 80 , Vicia faba in Ethiopia and China 78 , 81 . The concatenated analysis of recA - atpD showed that all these strains formed a highly bootstrapped cluster with R. hidalgonense FH14 T and displayed high nucleotide identities of recA - atpD (> 99.4%).…”
Section: Resultsmentioning
confidence: 99%
“…Noteworthy, strains closely related to R. hidalgonense have also been isolated from other legumes including Acacia gummifera 78 , Indigofera arrecta in Ethiopia 3 , Trifolium spp. in Ethiopia 79 , T. semipilosum in Kenya 80 , Vicia faba in Ethiopia and China 78 , 81 . The concatenated analysis of recA - atpD showed that all these strains formed a highly bootstrapped cluster with R. hidalgonense FH14 T and displayed high nucleotide identities of recA - atpD (> 99.4%).…”
Section: Resultsmentioning
confidence: 99%
“…These efficient bacteria are indicated as plant growth-promoting rhizobacteria (PGPR) [ 12 ]. Seed inoculation with PGPR that can colonize plant roots enhances seed germination rate [ 13 ], root growth and plant development under salt stress as a consequence of its potential in a symbiotic N 2 fixation, and root hydraulic conductivity [ 14 ], production of plant hormones like auxins, cytokinins and gibberellins as well as production of 1-aminocyclopropane-1-carboxylate deaminase [ 15 ], maintaining a high K + /Na + ratio, scavenging reactive oxygen species (ROS), stimulating the activity of soil enzymes [ 16 ], and enhancing soil physicochemical properties [ 17 ]. Consequently, a profitable strategy to mitigate the harmful impacts of salt stress with an increase in plant growth could be the co-inoculation of seeds with different PGPR strains [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…It plays a key role in soil fertility restoration through nitrogen fixation by its successful association with Rhizobium sp. (root nodulation bacterium), therefore making a significant contribution to agricultural sustainability [7].…”
Section: Introductionmentioning
confidence: 99%